Biodiversity assessment of specially protected natural areas in the steppe zone: CIBI methodology (Journal of Geography and Environmental Management, 2026)
Currently, biodiversity is declining due to climate change and anthropogenic pressure. The aim of this study is to develop a comprehensive methodology for assessing the biodiversity of specially protected natural areas (SPNAs). Due to the lack of a unified spatial-quantitative methodology, the original Composite Index of Biodiversity Integrity (CIBI) methodology was developed during the study. The methodology combines five parameters: total species richness (S), proportion of Red Book species (R), species density (D), proportion of high-vegetation areas (V), and SPNA age (Y). Weight coefficients were determined based on Saaty's Analytic Hierarchy Process. Using geographic information systems and remote sensing technologies based on Sentinel-2 satellite imagery (2023–2025 vegetation season), 22 SPNAs (47,903.5 km²) were analyzed. According to the results, the territories were classified into four categories: high biodiversity (CIBI > 0.40; 1 SPNA – Naurzum State Nature Reserve), medium level (0.31–0.40; 5 SPNAs), low level (0.20–0.30; 11 SPNAs), and very low level (< 0.20; 5 SPNAs). A moderate positive correlation was found between NDVI and species richness (r = 0.58; p < 0.01). The scientific significance of the study lies in the first comprehensive assessment of SPNA biodiversity in Kazakhstan's steppe zone, and its practical value is in identifying priority conservation areas and enabling evidence-based decision-making in nature conservation policy.
Keywords: biodiversity; specially protected natural areas; CIBI index; NDVI; GIS; steppe ecosystems; remote sensing